Loose knots and surgical site infections in abdominal surgeries (clean-contaminated and contaminated wounds) - Madhusudhan, Napa; Prabhakar, R. (International Surgery Journal, 2021)
Background: Surgical site infections (SSIs) are associated with high healthcare costs and worsen the post-operative course of a considerable proportion of general abdominal surgical patients. SSIs raise the risk of post-operative morbidity and mortality, necessitating hospitalization, intravenous antibiotics, and potentially surgical reintervention. The aim of the study was to compare the outcome of intermittent loose knots and the conventional vertical mattress suturing in patients undergoing abdominal surgeries. Methods: This prospective comparative study was done in patients undergoing emergency abdominal surgeries for any cause. Patients were divided into 2 groups- (a) group 1 (45 patients): intermittent loose knots between conventional vertical mattress sutures; (b) group 2 (45 patients): conventional vertical mattress suturing. Results: In this study, 31% of patients were in the 41-50 years age group, 53.3% of patients were male. Among various abdominal surgery opted, laparotomy was the most commonly performed procedure (47%). In this study, group 1 patients shown a decrease in wound gap, secondary wound closure and delayed wound approximation than group 2 patients. Conclusions: Loose knots in between conventional vertical mattress sutures are better than conventional vertical mattress suturing in terms of wound gap, secondary wound closure and delayed wound approximation.